Effects of Zr on high temperature deformation and dynamic precipitation of laves phase in Fe–13Cr–5Al–2Mo–0.5Nb–0.4Ta alloy - Wenbo Liu (Results in Physics, 2021)
High temperature deformation of Fe–13.5Cr–4.7Al–2.0Mo–0.70Nb–0.40Ta (FeCrAl) and Fe–13.5Cr–4.7Al–2.0Mo–0.45Nb–0.4Ta–0.11Zr (FeCrAl–Zr) alloys was performed at temperatures of 800–1100 °C with the strain rates of 0.01–10 s−1, and the constitutive model was established based on the Arrhenius equation. True strain-stress curves showed dynamic softening in FeCrAl and FeCrAl–Zr alloys. The maximum activation energy showed significantly different bteween FeCrAl (313 kJ/mol) and FeCrAl–Zr (627 kJ/mol) alloys. Due to the stabilizing effect of Zr on Laves phase, precipitate free zone (PFZ) in FeCrAl–Zr alloy was wider than that in FeCrAl alloy at the same strain rate. Low-angle grain boundary (LAGB) and coincident site lattice (CSL) grain boundary both increased in the FeCrAl–Zr alloy.